РОЗЧЛЕНУВАННЯ ПЛІОЦЕН-ЧЕТВЕРТИННИХ ВІДКЛАДІВ ЧОРНОГО МОРЯ (ПІВНІЧНИЙ ШЕЛЬФ) ЗА ОСТРАКОДАМИ - Dykan, N. (Institute of Geological Sciences of the Ukrainian National Academy of Sciences, 2012)
The regularities of stratigraphic position of fossil ostracodes are analysed in the deposits of north shelf of the Black sea (Ukrainian shelf from the Danube’s delta to the Kerch channel, the basins of estuaries of north-western coast of the Black sea, the key-sections of Kerch and Tamanian Peninsula). The lists of species composition of ostracodes and speciesindexes are given for all stratigraphic horizons of Pliocene-Quaternary deposits. Species composition of paleoassociations and its population dynamics in during to Pliocene- Holocene are analysed. The zoogeographic analysis of Pliocene-Quaternary ostracodes (species composition of the Mediterranean and Caspian ostracodes , recurrent ostracodes, time and the direction of its migrations in Mediterranean-Black Sea-Caspian area) are analyzing. At the first the local biostratigraphic subdivisions according to ostracodes (Complex-Zone, layers with ostracodes) were separated in Kimerian, Kujalnikian, Gurian, Chaudian, Old-Evksinian, Evksino-Uzunlarian, Karangatian, Postkarangatian, Novo- Evksinian, Holocene (Kalamitian) deposits. The criteria of marking the frontier between Pliocene and Quaternary, Neopleistocene and Holocene according to ostracodes were given.